THE THEME OF WAR IN THE LITERARY AND JOURNALISTIC WORKS OF JAVIER CERCAS (Based on the Novels «Soldiers of Salamina» and «The Speed of Light» and Columns in «El País Semanal») - Artemova, Lyudmila (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
Our research is focused on the comparative study of the narrative strategies of J. Cercas as a novelist and columnist. As a starting point, we have used the theme of war in his literary work (the Spanish Civil War) and in his columns (the war in Ukraine) in ‘El País Semanal’. We have come to discover that one of Cercas’s strategies is to contrast ideas at different textual levels in order to reveal different approaches. In the structure of the column, this strategy is revealed in the contrastive use (antithesis) of ‘I/we’ VS ‘the other/they’. ‘We’ is used both to refer to the writer with his circle of loyal readers, and ‘we – the Spaniards’, ‘we – the Europeans (including Ukrainians)’. On the syntactic level, we can see the parallel structures skillfully used by the author, which, as a counterpart, are invested in semantic oppositions. Thus, war is contrasted with peace, truth with lies. Among the concepts that we have included in this research that are so closely linked to the theme of war are homeland, patriotism and patriot. ______________ References: • Corredera González, M. (2010). La guerra civil española actual: silencio y diálogo entre generaciones (229 p.). Madrid: Iberoamericana. Retrieved from https://elibro.net/es/ ereader/ugr/174844 • Durán Mañas, M. (2023). Simetría y variación como técnica narrativa para la construcción del héroe en Soldados de Salamina de Javier Cercas. Revista chilena de literatura, (107), 313–329. Retrieved from https://digibug.ugr.es/bitstream/handle/10481/91922/Dur%c3%a1n _Ma%c3%b1as_Simetr%c3%ada%20y%20variaci%c3%b3n.pdf?sequence=1&isAllowed=y • Potok, M. (2017). Javier Cercas leído en Polonia. Políticas de la recepción. Sociocriticism, 32(1), 117–146. Retrieved from https://digibug.ugr.es/bitstream/handle/10481/59430/6013-14110-1-PB.pdf?sequence=1&isAllowed=y • Pozo García, A. (2018). Personaje de sí mismo: verdad y mentira en la narración de Javier Cercas. Revista Internacional de Estudios Literarios, (15), 82–109. Retrieved from https://digibug.ugr.es/bitstream/handle/10481/51674/2.1%20POZO%20247.pdf? sequence=1&isAllowed=y • Zhu, J. (2020). La autoficción. Una investigación teórica y un ejemplo en las narraciones de Javier Cercas (Doctoral dissertation, Universidad de Granada, 320 p.). Retrieved from https://digibug.ugr.es/bitstream/handle/10481/62886/68979.pdf?sequence=4&isAllowed=y Material ilustrativo: • Cercas, J. (2001). Soldados de Salamina. Barcelona: Tusquets Editores. • Cercas, J. (2005). Velocidad de la luz. Barcelona: Tusquets Editores. • Cercas, J. (2022, May 1). A los ucranios, que les zurzan. El País Semanal, p. 6. • Cercas, J. (2022, Nov 14). Dave Eggers y el patriotismo. El País Semanal, p. 6. • Cercas, J. (2022, May 14). Katja Petrowskaya, bañada en lágrimas. El País Semanal, p. 6. • Cercas, J. (2022, Dec 11). La gran revolución. El País Semanal, p. 6. • Cercas, J. (2021, Nov 14). La invención del pasado. El País Semanal, p. 8. • Cercas, J. (2024, May 25). Las preguntas del pacifismo. El País Semanal, p. 6. • Cercas, J. (2022, Apr 4). No pasarán. El País Semanal, p. 6. • Cercas, J. (2022, Feb 2). ¿Qué es la guerra? El País Semanal, p. 8. • Cercas, J. (2022, Oct 16). ¿Qué fue de Julián Rodríguez? El País Semanal, p. 6. • Cercas, J. (2022, Mar 20). Vindicación de la patria. El País Semanal, p. 8. • Cercas, J. (2023, Jun 25). Una gran ocasión. El País Semanal, p. 6.